Validity of Sinergi Learning Model (Science Process Skills Integration with Local Wisdom and Technology) - Fitriani, Herdiyana; Tika, I Nyoman; Artawan, Putu; Arnyana, Ida Bagus Putu; Adnyana, Putu Budi; Citrawathi, Desak Made (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2025)
This study aims to validate the SINERGI (Science Process Skills Integration with Local Wisdom and Technology) learning model, which is designed to improve students' Science Process Skills (SPS) through the integration of local wisdom and technology. Validation was carried out by involving five education experts to assess the validity of the content and construct of the model. Content validity covers six main aspects, namely supporting theory, syntax, social system, reaction principle, support system, and model implementation, while construct validity covers seven aspects, including components of the learning model. The validation results show that the SINERGI learning model has a high level of validity with most indicators in the very valid category and reliability above 85% based on the Percentage of the Agreement method. This finding confirms that the SINERGI learning model is feasible to be applied in 21st-century science learning, although minor improvements are needed in the reaction principle aspect.